Perbuatan melawan hukum PERBUATAN MELAWAN HUKUM OLEH PIHAK PENYELENGGARA PADA LAYANAN SECURITIES CROWDFUNDING ATAS RISIKO KERUGIAN INVESTASI TERHADAP PEMODAL SERTA PERLINDUNGAN HUKUMNYA: indonesia - rizky, Ichsan (Jurnal Hukum Respublica, 2023)
Unlawful acts committed by the organizers of Securities crowdfunding cause losses to investors. Therefore, this study serves to find out what legal protections are for investors for losses, using a normative juridical approach that is used to answer problems that occur in securities crowdfunding through consumer comments on the securities crowdfunding application. which causes investment losses to investors due to unlawful acts by the organizers Securities Crowdfunding both because of human resources and facilities factors, the role and position of the Financial Services Authority in the supervisory and regulatory functions of Securities Crowdfunding, the role and position of the Financial Services Authority in the supervisory and regulatory functions of Securities Crowdfunding. As well as legal protection for investors, legal protection both preventive and sanctions.